Biosensing the Histamine Producing Potential of Bacteria in Tuna - Trevisani, Marcello; Cecchini, Matilde; Fedrizzi, Giorgio; Corradini, Alessandra; Mancusi, Rocco; Tothill, Ibtisam E. (Frontiers in Microbiology, 2019)
Histamine poisoning is the most common cause of human foodborne illness due to the consumption of fish products. An enzyme-based amperometric biosensor was developed to be used as a screening tool to detect histamine and histamine-producing bacteria (HPB) in tuna. It was developed by immobilizing histidine decarboxylase and horseradish peroxidase on the surface of screen-printed electrodes through a cross-linking procedure employing glutaraldehyde and bovine serum albumin. The signal generated in presence of histamine at the surface of the electrode was measured by chronoamperometry at in presence of a soluble redox mediator. The sensitivity of the electrode was 1.31-1.59 µA/mM, with a linear range from 2 to 20 µg/ml and detection limit of 0.11 µg/ml. In this study fresh tuna fillets purchased in supermarkets in different days (n=8) were analyzed to detect HPB. Samples with different concentration of histamine were analyzed with culture-based counting methods, biosensor and HPLC and also a challenge test was made. Recovery of histamine from cultures and tuna samples was also assessed. The presence of Morganella psychrotolerans, Photobacterium phosphoreum, P. damselae and Hafnia alvei was detected using culture- and PCR-based methods. At the time of purchase these tuna samples had histamine concentrations from below the limit of detection (LOD) to 60 µg/g. HPLC and biosensor methods provided similar results in the range from zero to 432 µg/g (correlation coefficient, R2 = 0.990) and the recovery of histamine from cultures and tuna samples was very high (mean bias -12.69 to 1.63%, with root-mean-square error <12%). These results clearly show that fresh tuna is commonly contaminated with strong HPB. The histamine biosensor can be used by the Food Business Operators as a screening tool to detect their presence and to determine whether their process controls are adequate or not.